Faktor - Faktor yang Berhubungan dengan Burnout Perawat Pelaksana di Ruang Rawat Inap RSJ Provinsi Kalimantan Barat Tahun 2015 - Eliyana, Eliyana (Jurnal ARSI : Administrasi Rumah Sakit Indonesia, 2016)
The study aims to determine the relationship between demographic factors, personal factors and organizational factors toward burnout of nurses in the inpatient unit RSJ West Kalimantan Province. It is a quantitative study with cross-sectional approach using MBI (Maslach Burnout Inventory) instrument. Samples are the total population amounted to 122 nurses. The results showed that 82.8% are nurses with low category of burnout while 17.2% in middle category of burnout. The most dominant variables related to burnout is the workload of nurses.